Analisis Layanan Kinerja Sistem Informasi E-Registration (EREG) Menggunakan Metode Customer Satisfaction Index (CSI) Dan Importance Performance Analysis (IPA) - Efendi, Rusdi; Anggariani Rahayu , Devi; Setiawan, Yudi (Indonesian Journal of Computer Science and Engineering, 2024)
Taxes are the largest source of revenue for the state, so the government, in this case, the Directorate General of Taxes (DGT), continues to increase public awareness to fulfil its tax obligations. One of the efforts made by the DGT is the application of an information system in the registration of taxpayers to obtain a Taxpayer Identification Number (NPWP). The Bengkulu Pratama Tax Service Office (KPP) has used many systems for the job page at the tax office, one of which is the web: Pajak.go.id. This study aims to identify the attributes that need to be developed and maintained in taxpayers, satisfaction in online NPWP registration using the Ereg system and to determine customer satisfaction with the Ereg system at KPP Pratama Bengkulu. The purpose of the analysis is to use the Customer Satisfaction Index (CSI) method, and the second objective is analyzed using the Importance Performance Analysis (IPA) method. Based on the consumer satisfaction index calculation, the CSI value on the Ereg system at KPP Pratama Bengkulu is 84.61%, meaning that taxpayers are very satisfied with the performance of the Ereg system. While the IPA method shows the average value of the overall performance level of the attributes is smaller than the average value of the importance level with an average level of 97%, but there are some attributes whose performance is felt to be lacking and need to be improved, namely the priority I quadrant which repaired and quadrant II that must be maintained.